Islamic and Buddhist perspectives on the issues of lesbian, gay, bisexual, and transgender (LGBT): an analysis - Ahmad, Mohd Firdaus; Abdul Rahim, Adibah (IIUM Press, International Islamic University Malaysia, 2017)
The issue of LGBT has been discussed by different experts and scholars from many perspectives and fields of study. However, these perspectives include only those which are considered scientific in nature while religion is always excluded from the discussion. This is due to the influence of secularism which urges the separation between worldly matters and religion. It has caused the process of elimination of religious influence from anything related to human activity and life. The scientific view on LGBT is a mere description without any attempt to derive any moral judgment. Consequently, although the practice of same-sex sexual activity has been proven to be hazardous to the physical and mental health of human beings, the issue is still not being considered as immoral as putting immoral status to it is considered to be immoral in the first place. The view of religion on the issue of LGBT needs to be re-emphasized as it will solve the problems in this matter.